Analysis of the Explosion of Dissimilar Steel Joints in the 1050MW USC Boiler. (October 2020) - Yang, Qingxu; Shi, Xiaoming; Yang, Chao; Yang, Xianbiao; Peng, Hongwei; Liu, Xubi; Wan, Yu; Zhang, Xiaokang
Abstract: The leakage of dissimilar steel welded joint near the third superheater occurred in a power plant boiler. Through the analysis of tube cutting sampling, it is considered that the welding quality of dissimilar steel joint is good, the dissimilar steel joint cannot bear the bending load, and the improper arrangement of weld joint position together cause the leakage. It is suggested that the welding joints of dissimilar steel should not be arranged in the position with complex structural stress in the design, and the inspection of anti-abrasion and anti-explosion blind area should be strengthened in the process of maintenance.